Plasticity of categories in speech perception and production. Issue 6 (3rd July 2022) - Lindsay, Shane; Clayards, Meghan; Gennari, Silvia; Gaskell, M. Gareth
ABSTRACT: While perceptual categories exhibit plasticity following recently heard speech, evidence of effects on production has been mixed. We tested the influences of perceptual plasticity on production with an implicit distributional learning paradigm. In Experiment 1, we exposed participants to an unlabelled bimodal distribution of voice onset time (VOT) using bilabial stop consonants, with a longer category boundary than is typical. Participants' perceptual category boundaries shifted towards longer VOT, with a congruent increase in production VOT. Experiment 2 found evidence of perceptual transfer of these shifts to a different speaker and different syllables, and different words in production. Experiment 3 showed no shifts following exposure to a VOT boundary shorter than typical. We conclude that when listeners adjust their perceptual category boundaries, these changes may affect production categories, consistent with models where speech perception and production categories are linked, but with category boundaries influencing the link between perception and production.